2008
DOI: 10.4321/s0365-66912008000900005
|View full text |Cite
|
Sign up to set email alerts
|

Detección de glaucoma mediante telemedicina con SisGlaTel: satisfacción y aceptación entre los participantes y problemas detectados

Abstract: RESUMENPropósito: Evaluar las dificultades y el grado de aceptación y satisfacción entre la población participante durante una campaña de detección de glaucoma por telemedicina. Este trabajo es parte de un estudio global de desarrollo, aplicación y evaluación del SisGlaTel financiado por el Fondo de Investigaciones Sanitarias (FIS) y Pfizer Ophthalmics. Método: Se desarrolló un sistema de telemedicina sobre un programa específico en JAVA™. Se instaló la estación remota en el Centro de Atención Primaria. Los su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…The high level of patient satisfaction with the EQUALITY telemedicine program in the current study is consistent with other telemedicine glaucoma studies, 33 , 67 as well as with the literature regarding telemedicine used to diagnose diabetic retinopathy. 68 , 69 Patients also found it convenient to have their exam at the EQUALITY location, which could make it more likely that they will pursue eye care utilization using this model in the future, as the community-based eye care clinic is in close proximity to a large general retailer where patients routinely shop for necessary goods.…”
Section: Discussionsupporting
confidence: 91%
“…The high level of patient satisfaction with the EQUALITY telemedicine program in the current study is consistent with other telemedicine glaucoma studies, 33 , 67 as well as with the literature regarding telemedicine used to diagnose diabetic retinopathy. 68 , 69 Patients also found it convenient to have their exam at the EQUALITY location, which could make it more likely that they will pursue eye care utilization using this model in the future, as the community-based eye care clinic is in close proximity to a large general retailer where patients routinely shop for necessary goods.…”
Section: Discussionsupporting
confidence: 91%
“…It would be useful to know the converse, that patients seen in person would feel equally well supported if they had the ophthalmologist input to their care via a virtual clinic evaluation. A Spanish study by Blázquez et al 7 reported high levels of patient satisfaction with a telemedicine glaucoma screening program among an at-risk population but this is the first study we are aware of that looks at the satisfaction of patients reviewed virtually who have already been referred into the hospital eye care setting compared to the traditional standard clinic format.…”
Section: Discussionmentioning
confidence: 93%
“…Physician supervision may be reduced to quality control and confirmation of abnormal imaging results, which may significantly decrease assessment time and cost. De Mul et al showed that GDx images obtained and filtered by optometrists are useful for glaucoma screening by telemedicine, 10 while Blazquez et al, 11 Ohkubo et al, 8 and Toth et al 9 reported the usefulness of HRT for glaucoma screening.…”
Section: Introductionmentioning
confidence: 99%